2010
DOI: 10.3390/ijerph7030938
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Geomagnetic Field Influence on Gene Expression Using Influenza as a Model System: Basics of Physical Epidemiology

Abstract: Recent studies demonstrate distinct changes in gene expression in cells exposed to a weak magnetic field (MF). Mechanisms of this phenomenon are not understood yet. We propose that proteins of the Cryptochrome family (CRY) are “epigenetic sensors” of the MF fluctuations, i.e., magnetic field-sensitive part of the epigenetic controlling mechanism. It was shown that CRY represses activity of the major circadian transcriptional complex CLOCK/BMAL1. At the same time, function of CRY, is apparently highly responsiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 94 publications
0
36
0
Order By: Relevance
“…Because each electron spin has an associated magnetic moment, the interconversion and chemical fates of the singlet and triplet states can be influenced by the internal (field generated by magnetized IONPs) and external MF. 58 The interconversion from a triplet to a singlet state by the MF leads to spin relaxation, which is a time-dependent process interfering with the reactive behavior of an excited triplet state ( Figure 7B). Thus, interaction between the triplet state and biomolecules in cells may be significantly reduced, leading to decreased generation of free radicals.…”
mentioning
confidence: 99%
“…Because each electron spin has an associated magnetic moment, the interconversion and chemical fates of the singlet and triplet states can be influenced by the internal (field generated by magnetized IONPs) and external MF. 58 The interconversion from a triplet to a singlet state by the MF leads to spin relaxation, which is a time-dependent process interfering with the reactive behavior of an excited triplet state ( Figure 7B). Thus, interaction between the triplet state and biomolecules in cells may be significantly reduced, leading to decreased generation of free radicals.…”
mentioning
confidence: 99%
“…His results for the years 1880 and earlier were largely the same as those of Yeung . Furthermore, researchers have recently proposed that influenza pandemics may be associated with oscillations in body concentrations of vitamin D and solar cycle‐dependent fluctuations in the geomagnetic field .…”
Section: Resultsmentioning
confidence: 68%
“…Correlations have also been reported between solar cycles and longevity [34], although such findings remain equivocal [35]. A further series of studies have revealed associations between the solar cycle and flu pandemics [36], and a similar relationship was recently reported with papillomavirus infections [37]. Relationships have also been observed between GMA and sudden infant death syndrome [38] and epilepsy [39].…”
Section: Introduction (A) Geomagnetic Navigation In Animalsmentioning
confidence: 81%